2012
DOI: 10.2337/dc11-2202
|View full text |Cite
|
Sign up to set email alerts
|

Role of Muscle Mass and Muscle Quality in the Association Between Diabetes and Gait Speed

Abstract: OBJECTIVEOlder people with type 2 diabetes are at high risk of mobility disability. We investigated the association of diabetes with lower-limb muscle mass and muscle quality to verify whether diabetes-related muscle impairments mediate the association between diabetes and low walking speed.RESEARCH DESIGN AND METHODSWe performed a cross-sectional analysis of 835 participants (65 years old and older) enrolled in the InCHIANTI (Invecchiare in Chianti, aging in the Chianti area) population-based study. Total, mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
186
1
7

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(211 citation statements)
references
References 32 publications
17
186
1
7
Order By: Relevance
“…In this regard, previous studies linking diabetes with reduced walking speed (39,(43)(44)(45) have attributed this association to the accelerated loss of skeletal muscle strength that is commonly seen in older adults with this metabolic disease (23,24). To address whether diabetes-related muscle impairments could mediate the association between diabetes and low walking speed, researchers from the InCHIANTI study assessed walking performance and lower-extremity muscle mass, strength and power in a sample of 835 older adults (43).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, previous studies linking diabetes with reduced walking speed (39,(43)(44)(45) have attributed this association to the accelerated loss of skeletal muscle strength that is commonly seen in older adults with this metabolic disease (23,24). To address whether diabetes-related muscle impairments could mediate the association between diabetes and low walking speed, researchers from the InCHIANTI study assessed walking performance and lower-extremity muscle mass, strength and power in a sample of 835 older adults (43).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that aging patients with type 2 diabetes exhibit greater declines in muscle strength and functional capacity and more rapid loss of muscle mass than normoglycemic controls (Park et al 2007;Garg et al 2009;Leenders et al 2013;Volpato et al 2012). Indeed, diabetes complications such as peripheral vascular disease and peripheral neuropathy are associated with poor gait ability, impaired balance, and increased risk of falls (Ko et al 2011;Powell et al 2006;Wray et al 2005;Oliveira et al 2012;Vinik et al 2015).…”
Section: Functional Capacity In Elderly Diabetic Patientsmentioning
confidence: 99%
“…The many complications associated with diabetes include cardiovascular diseases, peripheral neuropathy, retinopathy, chronic renal failure, and impaired mental health (Blaum et al 2007;Maiorana et al 2002;Reeves et al 2010), which put diabetic patients in a polypathological condition (i.e., when diabetes coexists with two or more other diseases, such as hypertension, chronic renal failure, depression, and ischemic heart disease) (Rodríguez-Mañas et al 2014). In elderly populations, diabetes is also associated with reduced muscle strength, poor muscle quality, and accelerated loss of muscle mass (Morley 2008;Garg et al 2009;Leenders et al 2013;Park et al 2007;Volpato et al 2012;Morley et al 2014). Indeed, diabetes mellitus and insulin resistance increase the risk for accelerated aging and for the development of frailty syndrome (Kahn 2007;Sinclair et al 2012;Volpato et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the various micro and macrovascular diseases which contribute to disability amongst patients with T2DM, in older people with diabetes, physical frailty and sarcopenia are now emerging as a third category of complications [144][145][146]. Numerous observational studies have reported that older adults with T2DM are at risk of an accelerated decline SMM, muscle strength and/or higher odds of impaired physical functioning relative to their nondiabetic counterparts [147][148][149][150][151][152][153][154][155][156][157][158]. Despite the plethora of evidence, the biological mechanisms are uncertain and still under investigation.…”
Section: Implications For Future Research and Conclusionmentioning
confidence: 99%